ANALYSIS OF POLITENESS STRATEGIES IN THE FILM JALAN YANG JAUH, JANGAN LUPA PULANG DIRECTED BY ANGGA DWIMAS SASONGKO: Analisis Strategi Kesantunan Berbahasa dalam Film Jalan Yang Jauh, Jangan Lupa Pulang Karya Angga Dwimas Sasongko - Abdul Malik; Fabio Testy Ariance Loren; Dody Irawan; Ahada Wahyusari; Siti Habiba; Mesiyatul Aini (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to describe the politeness strategies used in the film Jalan yang Jauh, Jangan Lupa Pulang directed by Angga Dwimas Sasongko. The research applies a descriptive qualitative approach. Data were collected through observation and note-taking techniques. The data consist of character utterances containing politeness strategies. The analysis refers to Brown and Levinson’s theory, which categorizes politeness strategies into five types: positive politeness, negative politeness, bald on record, off record, and inner speech. The findings show that all five types of strategies are present in the film, with positive politeness being the most dominant. This indicates that the characters in the film tend to use communication that builds closeness, fosters familiarity, and maintains social relationships. The study also suggests that films can serve as educational media in developing awareness of polite language in everyday life.